Fintech Disruption: Implications for Traditional Banking and Financial Institutions - Hidayat, Randy (Penelitian dan Pengembangan Ilmu, 2024)
Fintech disruption has emerged as a significant force overhauling the landscape of traditional banking and financial institutions. Fintech startups, leveraging advanced technologies such as artificial intelligence, blockchain and big data analytics, are challenging incumbents by offering innovative customer-centric solutions. This research aims to explore how the integration of fintech technology affects the operational efficiency and profitability of traditional banking. The research method used is a systematic literature review with the PRISMA approach, collecting and analyzing articles from reputable databases. The research results show that fintech improves operational efficiency and profitability of traditional banks, but also poses challenges in terms of technology adoption and changes in consumer behavior. The implications of this research include the need for adaptation strategies for traditional banks and regulatory policy updates to support fintech innovation.